From Cells to Structures to Evolutionary Novelties: Creating a continuum - Boisvert, Catherine (Springer, 2013)
This thematic issue addresses questions of constraints on the evolution of form—physical, biological, and technical. Here, form is defined as an embodiment of a specific structure, which can be hierarchically different yet emerge from the same processes. The focus of this contribution is about how developmental biology and paleontology can be better integrated and compared in order to produce hypotheses about the evolution of form. The constraints on current EvoDevo research stem from the disconnect in the focus of study for developmental geneticists and evolutionary morphologists; the former being interested in early developmental events at a molecular level in a model animal, the latter in late developmental events or comparison between adult forms, at a structural level in non-model animals. In order to truly integrate information from both fields in our understanding of evolutionary processes, morphology needs to be reintegrated in the study of gene expression, and its time frame needs to be extended beyond early developmental stages. Gene expression in non-model organisms also needs to be studied in order to gain perspective into primitive patterning at evolutionary nodes. Hypotheses formed by the comparison of expression patterns and morphologies seen in extant species can then be tested against forms found in the fossil record, coming closer to understanding the mechanisms underlying evolution.